Waste less time on Facebook — follow Brilliant.
×

Need help with limits

If \(\left( 1 + \sqrt{3} \right)^n = A + B\sqrt{3}\), show that the limit of \(\frac{A}{B}\) as \(n\) approaches infinity is equal to sqrt(3).

Note by Haris Bin Zahid
4 years, 1 month ago

No vote yet
3 votes

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

It must be \(\sqrt{3}\) rather. Two ways to solve: \((1 + \sqrt{3})^n = \displaystyle \sum_{r = 0}^{n} {n \choose r}({\sqrt{3}})^r = A + B\sqrt{3} \)

\((1 - \sqrt{3})^n = \displaystyle \sum_{r = 0}^{n} {n \choose r}({-\sqrt{3}})^r = A - B\sqrt{3} \) (Check that \(B\) comes from odd powers and \(A\) from even)

Solve to get :

\(A = \frac{(1 + \sqrt{3})^n + (1 - \sqrt{3})^n}{2}\) ,

\(B = \frac{ (1 + \sqrt{3})^n - (1 - \sqrt{3})^n}{2\sqrt{3}}\)

Now, \(\displaystyle \lim_{n \to \infty} \frac{A}{B}\)

= \(\frac{\frac{(1 + \sqrt{3})^n + (1 - \sqrt{3})^n}{2}}{\frac{ (1 + \sqrt{3})^n - (1 - \sqrt{3})^n}{2\sqrt{3}}}\)

= \(\boxed{\sqrt{3}}\) . \(\Bigg(As \displaystyle \lim_{n \to \infty} \frac{(1 - \sqrt{3})^n}{(1 + \sqrt{3})^n} = 0 \Bigg)\)

\[ALTERNATE:\]

\(\displaystyle \lim_{n \to \infty} (1 - \sqrt{3})^n = \displaystyle \lim_{n \to \infty} A - B\sqrt{3} = 0 \) [As \(\displaystyle \lim_{n \to \infty} (1 - \sqrt{3})^n = 0\)]

\(\Rightarrow \displaystyle \lim_{n \to \infty} \frac{A}{B} = \boxed{\sqrt{3}}\)

This was less a limit than a binomial theorem question :)

Jatin Yadav - 4 years, 1 month ago

Log in to reply

Nice solution

Jagdish Singh - 4 years, 1 month ago

Log in to reply

Strangely, this reminds me of Pell's Equations.

Matthew Fan - 4 years, 1 month ago

Log in to reply

Not surprising. The integer solutions of the equation \[ x^2 - 2y^2 \; = \; \pm1 \] are precisely the integer coefficients \(x + y\sqrt{2} = \pm(1 + \sqrt{2})^n\) for \(n \in \mathbb{Z}\) (you get \(+1\) when \(n\) is even, and \(-1\) when \(n\) is odd). Similar games can be played with \(\sqrt{3}\).

Mark Hennings - 4 years, 1 month ago

Log in to reply

I'm assuming you mean \(A, B, n\) to be positive integers? Otherwise the problem is unsolvable.

Michael Tang - 4 years, 1 month ago

Log in to reply

It is not necessary ,

Sometimes we even calculate \(\displaystyle \lim_{n \to \infty} f(n!) \dots \) .

Jatin Yadav - 4 years, 1 month ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...